Analisis Pengendalian Kualitas Produk Sanitary Ware Dengan Pendekatan Metode FMEA di PT. XYZ - Siregar, Khawarita; Siregar, Syahrul Fauzi (Media Teknika, 2016)
PT. XYZ is a company engaged in manufacturing of sanitary ware products. Various obstacles are faced by PT. XYZ in the course of its production, one of which is the problem of the quality of products produced from every production process. Based on historical data from July 2014 – June 2015, the percentage of defect for C models squat toilets reached 20.26%. The company  wants  the  upper  limit of  defects  products only  reached  12%  for  each  period of production. Based on previous research, there are two dominant types of defects are cracked/broken and uneven color. Therefore needed improvement through analysis of quality control approach FMEA method and ANOVA. The result of FMEA for cracked/broken defects obtained failure mode is the temperature and duration of combustion products are not appropriate (RPN numbers amounted to 648) and for uneven color obtained failure mode is glazed improper composition (RPN numbers of 576). This study also will provide corrective suggestions  through  the  design  of  experiments  by  ANOVA  method.  The  results  of  the experiment  with  the  design  of  interaction  factor  ANOVA  showed  that  long  combustion products,  glazed  composition  and  temperature  of  the  combustion  products  provide  a significant effect on the amount of product defects